Characterizing the release of bioactive N‐glycans from dairy products by a novel endo‐β‐N‐acetylglucosaminidase. (15th July 2015) - Karav, Sercan; Bell, Juliana Maria Leite Nobrega De Moura; Parc, Annabelle Le; Liu, Yan; Mills, David A.; Block, David E.; Barile, Daniela
<x xml:space="preserve">Abstract</x> Endo‐β‐N‐acetylglucosaminidase isolated from B. infantis ATCC 15697 (EndoBI‐1) is a novel enzyme that cleaves N‐N′‐diacetyl chitobiose moieties found in the N‐glycan core of high mannose, hybrid, and complex N‐glycans. These conjugated N‐glycans are recently shown as a new prebiotic source that stimulates the growth of a key infant gut microbe, Bifidobacterium longum subsp. Infantis. The effects of pH (4.45–8.45), temperature (27.5–77.5°C), reaction time (15–475 min), and enzyme/protein ratio (1:3, 000–1:333) were evaluated on the release of N‐glycans from bovine colostrum whey by EndoBI‐1. A central composite design was used, including a two‐level factorial design (24) with four center points and eight axial points. In general, low pH values, longer reaction times, higher enzyme/protein ratio, and temperatures around 52°C resulted in the highest yield. The results demonstrated that bovine colostrum whey, considered to be a by/waste product, can be used as a glycan source with a yield of 20 mg N‐glycan/g total protein under optimal conditions for the ranges investigated. Importantly, these processing conditions are suitable to be incorporated into routine dairy processing activities, opening the door for an entirely new class of products (released bioactive glycans and glycan‐free milk). The new enzyme's activity was also compared with a commercially available enzyme, showing that EndoBI‐1 is more active on native proteins than PNGase F and can be efficiently used during pasteurization, streamlining its integration into existing processing strategies. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1331–1339, 2015